Meaning for the professional practice of terms attributed to actions of nursing - a descriptive study - Greicy Kelly Gouveia Dias Bittencourt; Maria Miriam Lima da Nóbrega (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Study of the descriptive exploratory type developed with the objective to identify to the meaning of the terms used in the registers of nursing in six clinical units of a hospital school and to confirm the meaning of the same ones. The collection of data was carried through of March the April of 2005, when was requested that the nurses marked if they agreed or if they disagreed with the definition of the 74 enclosed terms in the axes type of action. It was gotten, as resulted, one IC ≥0,80 for 69 terms and IC <0,80 for 5 terms. We conclude that meaning of the terms used for the nurses of the HULW/UFPB are directed for actions commence exerted by the Nursing, inside of the concepts central offices of the Nursing Actions Classification of the CIPE Version Beta 2.